2006
DOI: 10.1021/la062573g
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Gluing and Postgluing of Langmuir−Blodgett Monolayers at Hydrocarbon Surfaces

Abstract: Langmuir-Blodgett (LB) monolayers of 5,11,17,23,29,35-hexaformyl-37,38,39,40,41,42-hexakis(1-n-octyloxy)calix[6]arene (2), deposited onto silylated silicon wafers, were cross-linked (i.e., "covalently glued") via Schiff base formation with poly(allylamine). Direct evidence for imine formation was obtained from X-ray photoelectron spectroscopy and from attenuated total reflection IR spectroscopy. These modified surfaces could be removed from the aqueous subphase into air with retention of the assembly and its o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Calix[n]arene derivatives can be deposited onto several solid substrates such as quartz crystal [51], mica [52], silicon [53], cadmium arachidate [54], silver [55] and ITO [56]. These studies showed that the deposition is strongly depend on the substrate surface.…”
Section: Atomic Force Microscopy Resultsmentioning
confidence: 99%
“…Calix[n]arene derivatives can be deposited onto several solid substrates such as quartz crystal [51], mica [52], silicon [53], cadmium arachidate [54], silver [55] and ITO [56]. These studies showed that the deposition is strongly depend on the substrate surface.…”
Section: Atomic Force Microscopy Resultsmentioning
confidence: 99%
“…Experimental methods that were used to (i) synthesize 5,11,17,23,29,35hexakis[(N,N,N-trimethylamonium)-N-methyl-37,38,39,40,41,42-hexakis-nhexadecyloxy-calix[6]arene chloride (i.e., Calix), (ii) deposit Langmuir-Blodgett (LB) bilayers of PAA-crosslinked Calix, 1 and 2 onto poly[1-(trimethylsilyl)-1-propyne] (PTMSP) supports or silicon wafers (silylated with n-octadecyltrichlorosilane, OTS), (iii) quantify gas permeabilities, and (iv) measure film thicknesses by ellipsometry were similar to those that have previously been described. [1][2][3] Ellipsometry measurements were made using VASE ellipsometer (J.A. Woollam Co., Inc., Lincoln, NE), equipped with variable wavelength ( from 250-1700nm) and angle of incidence (15º-90º) system, a λ of 632.8nm and an incidence angle of 70º were chosen for measurements.…”
mentioning
confidence: 99%
“…In order to demonstrate this concept, a calix [6]arene derivative was used as the bilayer-forming, water soluble, charged, amphiphile and poly(4-styrenesulfonate) (PSS) as the glue. [285][286][287] These glued bilayers are ultrathin with thicknesses of around 6 nm, although they are easy to prepare and process. They can be used as organic nanomembranes for gas separation applications since they exhibit remarkable permeation selectivity involving He, N 2 and CO 2 .…”
Section: Amphiphilic Assemblies For Novel Nanomembranesmentioning
confidence: 99%